Zinc Hydroxystannate Coated Nano-Magnesium Hydroxide as Flame Retardant for Semirigid Poly(vinyl chloride) - Xie, Jixing; Liu, Jianzhou; Xu, Jianzhong (Asian Journal of Chemistry, 2010)
ZnSn(OH)6 coated Mg(OH)2 (ZHS-MOH) was synthesized by a homogeneous precipitation method with ultrasonic and azeotropic technology. The results of XRD show that the characteristic diffraction peak of ZnSn(OH)6 advanced and the characteristic diffraction peak of Mg(OH)2 reduced respectively with increasing of the mass ratio of ZnSn(OH)6. The particle image of ZHS-MOH and Mg(OH)2 was observed by TEM. TGA and DTA showed the exothermic peak tempareture of Mg(OH)2 increased and the weight loss decreased. The ZHS-MOH was applied into semirigid PVC and it has a higher limiting oxygen index and lower SDR compared with that used Mg(OH)2.